Epidemiological trend of suicide in north of Iran from 2011 to 2018 with a focus on joinpoint regression - Sharareh Zabihi afroozi; Soraya Khafri; Aliasghar Manouchehri; Mahasti Emami; Hajar Alizadeh; Sussan Moudi; Sara Khaleghi (Babol University of Medical Sciences, 2023)
Background: Deaths due to potential suicide are preventable and this phenomenon is costly for the health care system and contradicts the values and cultural standards of an Islamic country. Methods: This study is a retrospective study. The research population includes all cases of suicide during the years 2011-2018 who were referred to the emergency department of Babol hospitals. The results were analyzed using SPSS v.23 and Joinpoint Trend Analysis software 4.9.0.0 to identify significant changes in the temporal trends of the outbreak. Results: The highest percentage of suicides occurred in summer (27.8%), on Saturdays (13%) and at night (53%). A total of 1.9% of the cases were commit suicides (leading to death). The highest frequency of suicide was shown in 1397 (21.2%) and the lowest in 1392 (5.1%) and was more common in women (68.2% vs. 31.8%). Suicide-related deaths was higher in the second four years (63.5%), but suicide rate was significantly higher in the first four years (2011-2014) and the mortality rate due to suicide was higher in men than women. Conclusion: Suicide attempts were higher in women than men but the death rate was higher in men which means that men attempt suicide more seriously than women. The model also predicted that suicide rates would rise in the coming years. For this reason, this important issue, along with a detailed analysis of the roots of suicidal ideation and preventive measures, should be considered by health officials and social institutions.